GAMBARAN TINGKAT KEPATUHAN MINUM OBAT ANTIHIPERTENSI DI PUSKESMAS JATINANGOR - Tsara Syarifah Istiqomah; Julia Ramadhanti; Kurnia Wahyudi (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2019)
Hypertension is the most common cardiovascular disease. This non-communicable disease cannot be cured but can be controlled by taking antihypertensive drugs regularly. Patient’s low compliance can be one of the factors that aggravates the patient's condition. This study aims to describe the proportion of patient’s adherence for taking antihypertensive drugs in Puskesmas Jatinangor using the Eight-Items Morisky Medication Adherence Scale (MMAS-8) questionnaire. This study was hold between September 2017 and August 2018 and was described using descriptive analytical method with crosssectional study design. From 74 respondents who participated in this study, we obtained the data in the form of sex, age, education level, marital status, occupation, income, payment media, hypertension duration, number of drugs consumed, type of medication, and motivational support. The data showed that 74 hypertensive patients in Puskesmas Jatinangor have a high compliance on taking antihypertensive drugs. We expect the results of this study can increase public awareness about drug compliance, especially for antihypertensive drugs in the working region of Puskesmas Jatinangor.